The effects of resisted sled loading on sprint start kinematics - Maulder, P.; Bradshaw, E.; Keogh, J. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Alterations in sprint start kinematics during resisted sled sprinting with loads of 10% and 20% body mass (BM) of ten track sprinters was assessed. High-speed video footage was collected at 250 Hz for the start action with sagittal kinematic measures subsequently obtained using APAS motion analysis software. A repeated measure ANOVA determined if there was a significant (p < 0.01) interaction between the kinematics under the various loaded conditions. Resisted sled loading did not change sprint start performance (mean horizontal block acceleration) but it did stimulate some key technical aspects such as start time and block push-off angle. Stimulating these two aspects of sprint start performance may lead to an enhanced sprint start, through a larger generation of force within the starting blocks and a more horizontal leaving position from the blocks.